Assessment of synergistic activity of rhamnolipid and linezolid against methicillin-resistant Staphylococcus aureus in-vitro and in-vivo with Galleria mellonella larvae model. (January 2023) - Kaskatepe, Banu; Ozturk, Sukran
Abstract: Antibiotic resistance, one of the most crucial public health problems, has increased the interest in synergy studies of antibiotics with existing antibiotics and natural compounds to make current treatment more effective in addition to new drug development. In this study, the effectiveness of rhamnolipid and linezolid on the Galleria mellonella larvae model in-vitro and in-vivo against Methicillin-resistant Staphylococcus aureus isolates, which are problematic in treatment, were investigated. Four S. aureus (One ATCC 29213 strain and three methicillin-resistant strains) were used in the study. Two MRSA isolates were resistant to linezolid, and one was susceptible. Partial synergy was observed in one resistant strain, and although no synergy was observed in the other resistant strain, the minimum inhibitory concentration of the resistant strain decreased from 16 to 4 μg/mL with a four-fold decrease and reached the susceptibility limit. No change was observed in the MIC of linezolid-susceptible strains. The G. mellonella larval model demonstrated that combined therapy was more effective than monotherapy by survival function tests and CFU determination. RML/LNZ combination improved survival compared to monotherapy and decreased the bacterial burden from 10 8 to 10 3 . Highlights: MRSA infection is one of the leading causes of hospital-acquired infections. MIC value of the MRSA strain decreased four-fold with RML/LNZ combination. RML/LNZ combination improved survival compared to monotherapy. RML/LNZ combination decreased the bacterial burden from 10 8 to 10 3 .